Protecting Critical National Infrastructure Against Cyber Operations Under International Humanitarian Law: Lessons for Southeast Asia - Andi Agus Salim; Maulidina Sari; Nova Bela Dhyta; Ahmad Sholihin Muttaqin; Try Hardyanthi (Universitas Negeri Semarang, 2026)
The rapid evolution of digital technology has significantly reshaped the dynamics of modern armed conflict, most notably through the escalating threat of cyberattacks against critical infrastructure. Essential facilities such as power grids, medical centers, water sanitation systems, and communication networks play an indispensable role in ensuring the safety and well-being of the civilian population. When such infrastructure is targeted during armed conflict, whether by State or non-State actors, the resulting humanitarian consequences can be catastrophic and far-reaching. International Humanitarian Law (IHL), which traditionally governs the protection of civilian objects, has yet to explicitly address the unique challenges posed by the digital frontier, particularly regarding the protection of critical infrastructure from cyber warfare. This research aims to critically examine the extent to which IHL principles can provide adequate protection for critical infrastructure within the context of cyber operations, while identifying the normative gaps that emerge in their implementation. Employing a doctrinal legal research methodology complemented by an interdisciplinary analytical approach integrating international legal analysis with cybersecurity contemporary military studies, and supported by selected contemporary cyber incidents, this study proposes a strengthened normative framework that is more responsive to the exigencies of the digital age. The novelty of this research lies in its specific focus on the protection of vital civilian infrastructure in modern warfare from an IHL perspective, offering legal solutions grounded in state practice and fundamental humanitarian principles. It further highlights the relevance of these normative developments for Southeast Asia by identifying legal and policy lessons that can strengthen regional preparedness for protecting critical infrastructure against cyber operations during armed conflict.